IMPACT RANGE ESTIMATION OF POLLUTED SOIL AREA FOR RADIATION MONITORINGBY «IN SITU» METHOD - A. Zhukouski; S. Kutsen; A. Khrutchinsky; A. Tolkachev; V. Guzov; V. Kojemiakin; V. Chudakov (Приборы и методы измерений, 2015)
Intensity of «direct» gamma-quanta absorbed in cylindrical detector has been determined for the detector placed over soil uniformly contaminated in depth. The dependence of impact range radius for NaI(Tl) detector to cesium depth contamination is established for soil from Tohoku region, Japan.